Assessment of left ventricular function and volumes by myocardial perfusion scintigraphy - comparison of two algorithms - Zajic, T.; Fischer, R.; Saurbier, B.; Brink, I.; Moser, E.; Krause, T. (Nuklearmedizin - NuclearMedicine, 2001)
Aim: Left ventricular volume and function can be computed from gated SPECT myocardial perfusion imaging using Emory Cardiac Toolbox (ECT) or Gated SPECT Quantification (GS-Quant). The aim of this study was to compare both programs with respect to their practical application, stability and precision on heart-models as well as in clinical use. Methods: The volumes of five cardiac models were calculated by ECT and GS-Quant. 48 patients (13 female, 35 male) underwent a one day stress-rest protocol and gated SPECT. From these 96 gated SPECT images, left ventricular ejection fraction (LVEF), end-diastolic volume (EDV) and end-systolic volume (ESV) were estimated by ECT and GS-Quant. For 42 patients LVEF was also determined by echocardiography. Results: For the cardiac models the computed volumes showed high correlation with the model-volumes as well as high correlation between ECT and GS-Quant (r ≥ 0.99). Both programs underestimated the volume by approximately 20-30% independent of the ventricle-size. Calculating LVEF, EDV and ESV, GS-Quant and ECT correlated well to each other and to the LVEF estimated by echocardiography (r ≥ 0.86). LVEF values determined with ECT were about 10% higher than values determined with GS-Quant or echocardiography. The incorrect surfaces calculated by the automatic algorithm of GS-Quant for three examinations could not be corrected manually. 34 of the ECT studies were optimized by the operator. Conclusion: GS-Quant and ECT are two reliable programs in estimating LVEF. Both seem to underestimate the cardiac volume. In practical application GS-Quant was faster and easier to use. ECT allows the user to define the contour of the ventricle and thus is less susceptible to artifacts.
Keywords: Myocardial perfusion scintigraphy; gated SPECT; left ventricular volumes; left ventricular function; Tc-99m-MIBI